Analysis of the Impact of Financial Technology and Financial Literacy on MSME Business Sustainability - Andini Nurwulandari (Lead Journal of Economy and Administration, 2023)
The purpose of this study is to investigate, from a monetary point of view, how the adoption of technology and increased levels of financial literacy affect the continued viability of micro, small, and medium-sized enterprises. In this study, a quantitative methodology is utilized by selecting a sample of 42 culinary MSMEs located in the Sumedang district. The data that were collected were examined utilizing approaches that involved multiple regressions. According to the findings of the study, the application of technology as well as an understanding of financial concepts has a materially beneficial effect on the long-term viability of micro, small, and medium-sized enterprises (MSME). Technology may be of assistance to micro, small, and medium-sized enterprises (MSMEs) in enhancing their levels of efficiency and production, while financial literacy may be of assistance in fostering improved levels of financial management and improved decision-making. This sends a message to the government in its role as a regulator, to academics in their role as educators, to the business sector in its role as a catalyst, and to the community in its role as a driver to promote and grow financial literacy and fintech for MSMEs in Sumedang Regency.